In vitro response of P.falciparum to chloroquine, amodiaquine, quinine and sulfadoxine/pryrimethamine in Ghana. - Akanmori, B.D.; Afari, E.A.; Nakano, T.; Ofori-Adjei, D.; Gyan, B.; Owusu-Adjei, S.; Adjei, A.A. (Ghana Medical Journal, 1989)
In Vitro asexual parasite sensitivity to chloroquine, amodiaquine, quinine, and sulfadoxine/pyrimethamine (SDZ/PYR) combination was determined for Plasmodium falciparum isolates from children in three schools at Nima (Urban), Madina (Peri urban) and Gomoa Fetteh (Rural), during the rainy season. Chloroquine resistance was present in 625% of children at Nima, 69.6% (23136) of children at Madina and 50% (16132) of those in Gomoa Fetteh. Resistance of P. falciparum to amodiaquine was recorded in 30% (6/20),35.7% (5/14) and 12.5% (1/8) of children in Nima, Madina and Gomoa Fetteh respectively. In addition parasite resistance to SDX/PYR was found in children in Nima, Madina and in one child at Gomoa Fetteh. Resistance to both chloroquine and amodiaquine was present in 3 children at Nima, 5 at Madina and in a single child at Gomoa Fettteh. Resistance to both chloroquine and SDX/PYR and to Amodiaquine and SDXIPYR was restricted to only Nima (2/15, 1/15) .and Madina 3/14, 2/15). There was no resistance to quinine in any of the areas studied. A progressive increase in minimum inhibitory concentrations (IC9O) for chloroquine was observed from Nima and Madina to rural Gomma Fetteh. Similarly, IC90 for amodiaquine was highest in Madina. The presence of multiple-drug resistant P. falciparum in these children represents a challenge to the control and management of falciparum malaria and this data serves as a baseline for monitoring any changes in parasite sensitivity to antimalarial drugs in the study areas
Journal Article
Keywords: Chloroquine; Quinine; Sulfadoxine/Pyrimethamine; P. falciparum; In vitro sensitivity